Peluang dan tantangan implementasi Personalisasi Pembelajaran berbasis Artificial Intelligence di Sekolah Dasar - Harsono, Arta Mulya Budi; Nafisah, Ainun; Noorhapizah, Noorhapizah; Agusta, Akhmad Riandy; Pratiwi, Diani Ayu (Universitas Muhammadiyah Magelang, 2025)
Learning in elementary schools needs to be tailored to students' needs to encourage active student engagement. However, in reality, learning is carried out by aligning student needs. The purpose of this study is to identify opportunities and challenges from various dimensions, ranging from technical to pedagogical to ethical, in AI-based personalized learning. The research method used is a literature review with the help of the Publish or Perish application. This research procedure consists of a database used to search for literature, search keywords, timeframe, inclusion criteria, and exclusion criteria for the literature. The results of this study are opportunities for AI-based personalized learning in elementary schools to accelerate academic mastery, optimize the role of teachers, increase student engagement, and encourage inclusion through dynamic cognitive load management. However, significant challenges related to the digital divide, teacher readiness, algorithmic bias, and the potential devaluation of holistic education threaten to exacerbate inequalities and erode the fundamental goals of education. The results of this study can contribute to educational transformation by integrating student learning needs with technology in the era of society 5.0.